Information processing theory and comprehension model in language learning: Experiences from future language teachers: a self-study research (Jóvenes en la Ciencia, 2021)
The objective of this research is to understand how the Information Processing Theory proposed by Atkinson and Shiffrin (1968) and the Language Comprehension Model proposed by Anderson (1995) affect language learning. The purpose of this paper is to identify the problems that the participants experienced during their language classes regarding retrieval of information, and comprehension issues presented in different language skills. The participants of this longitudinal self-study research project carried out over eight months are two students in a BA in English language teaching at the University of Guanajuato. The students were enrolled in foreign language learning classes; Japanese, French, and Sign Mexican language. Data were collected in a Sway portfolio, using reflective journal entries and visual evidence. The collected data presents results showing that receiving a different set of instructions affects the performance of holding information and the capacity to retrieve it back from the mental system. The analysis also shows that slow recognition of words in regard to listening and reading skills hinder language comprehension. This study has implications for language teaching in terms of bringing awareness of the cognitive mental processes that students go through when learning a language. Stimulating each stage of the models presented in this paper may increase the chances of success in the language.